AB1038 JUVENILE IDIOPATHIC ARTHRITIS INTO ADULTHOOD: HOW DO WE ASSESS DISEASE ACTIVITY?. (June 2019) - Priora, Marta; Peroni, Clara Lisa; Laganà, Angela; Borrelli, Richard; Fusaro, Enrico
Abstract : Background: Deepening the long-term study of Juvenile Idiopathic Arthritis (JIA) in adulthood is essential to increase the pathogenetic knowledge of the disease, to optimize the therapeutic choices accordingly, as well as to promote a more active communication between paediatric care and adult care specialists Objectives: The present project, created as part of the "transition of care", aims to compare clinimetric scores of wide use for adult inflammatory rheumatisms of the adult (DAS28, CDAI and SDAI) with the JADAS27 score, which has been validated and widely used in order to quantify JIA's activities in the paediatric field. As of today, adult patients with JIA are usually evaluated with clinimetric scores developed for adult chronic rheumatic diseases (DAS28, CDAI, SDAI) and there is no consensus concerning which of these scores doctors should favour, so that the choice is quite autonomous and varies from centre to centre. It is therefore of interest to verify whether among these indices of purely rheumatological use of adults there is one that is more appropriate than JADAS27 which can be useful in monitoring adult patients with JIA. Methods: The relevant clinical data were collected from 68 adult patients with JIA. A correlation analysis was performed between the clinimetric scores according to McNemar Test and Kappa by Cohen. Results: The results obtained suggest that none of the clinimetric scale commonly used in the rheumatological clinical practice of adult patients can completely replace JADAS27. DAS28 is the score that goes further from an acceptable correlation with JADAS. Since both CDAI and SDAI are calculated with formulas that are similar to the one used for JADAS (algebraic sums of affected joints, subjective outcomes reported by the patient, clinical judgment of the physician), they happen to be a method of quantification of disease activity quite closer to JADAS itself. The analyses outlined a scenario in which a much larger portion of patients are classified in remission stages or in low disease activity when using CDAI and SDAI compared to JADAS27. Conclusion: This element inspired us to consider how in paediatric age a more "demanding" attitude towards the disease led to the validation of both a score and its very stringent cut-offs which are functional to a treat to target characterized by a complete remission whose main goal is to avoid long-term sequelae. SDAI was found to be the scale of common use in the adult care that more properly approaches the clinometry validated for the paediatric population (JADAS27). Although clinical common sense should not distract from assessing disease activity in this specific patient population from a global perspective, such a study could suggest using SDAI as clinimetric score of choice in adult patients with JIA. Further checks in larger population samples are obviously necessary. References: [1] Oliveira-Ramos F, Eusébio M, et al. Juvenile idiopathic arthritis in adulthood: fulfilment of classification criteria for adult rheumatic diseases, long-term outcomes and predictors of inactive disease, functional status and damage. RMD Open.2016; (2) [2] Coulson EJ, Hanson HJM, et al. What does an adult rheumatologist need to know about juvenile idiopathic arthritis? Rheumatology. 2014;53(12). [3] Selvaag AM, Aulie HA, et al. Disease progression into adulthood and predictors of long-term active disease in juvenile idiopathic arthritis. Ann Rheum Dis. 2016;75(1) Disclosure of Interests: Marta Priora Grant/research support from: Sanofi SpA, Clara Lisa Peroni: None declared, Angela Laganà: None declared, Richard Borrelli: None declared, Enrico Fusaro Grant/research support from: Abbvie Abiogen Actelion Amgen Biogen BMS Celgene Grunenthal GSK Janssen Lilly MSD Mundipharma Novartis Pfizer Roche SANOFI SOBI UCB